KAJIAN EKSPERIMEN MENGENAI DISTRIBUSI LIQUID HOLD-UP POLA ALIRAN ANNULAR AIR-UDARA PADA PIPA HORISONTAL - , ANAM BAHRUL ULUM NAJIBULLOH; , Dr. Deendarlianto S.T., M.Eng, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Annular flow pattern is a pattern of two-phase flow, where the fluid surrounding the gas at the center of the pipe forming a ring-like pattern. Annular flow pattern can be found in the geothermal water collector system. The studies of this flow pattern in geothermal energy can be used to design the measuring instrument of two-phase flow that still uses a fairly expensive technology. Research on annular flow pattern is very important to do because there are still little database from previous studies. The purposes of this study are to determine the distribution of the liquid hold-up in the annular flow pattern flowing in a horizontal pipe. Two-phase flow measuring device with a conductance method called constant electric current method (CECM). CECM sensor made of brass metal and serves as an electrode placed between the transverse intersection of the pipe. The variation of superficial velocity is determined by making a plot on Mandhane flow pattern (Mandhane et al. 1974). The results of the researches show that the film layer of annular flow patterns in horizontal pipes tend to be thicker at the bottom surface of the pipe and thinner at the top surface of the pipe due to the effects of gravity. Movement pattern of liquid hold-up against the increase of superficial gas velocity variations would indicate a decreasing value of liquid hold-up as a result of thinner film layer formed on the surface of the pipe. Wave velocity and wave number will further increase due to increase of superficial gas velocity.